Early identification within inclusive early childhood curriculum: an ethnographic study from New Zealand. Issue 3 (17th February 2020) - Zhang, Qilong; Morrison, Val
ABSTRACT: Inclusive education has long been implemented in regular educational settings in many jurisdictions including New Zealand (NZ). Since many children with special educational needs (CSEN) are not identifiable in a family environment, to ensure all CSEN are supported in a timely manner, early identification should be an integral component of the inclusive curriculum. Adopting focused ethnography, this study investigated how CSEN were identified within the mandated national curriculum framework in a regular early childhood setting in NZ. The data analysis revealed: (1) A common belief about the importance of early identification was shared by the parents and teachers; (2) A three-step (noticing, assessing, referring, NAR) process of early identification was implemented; (3) The implementation of the NAR process was in compliance with the four principles of NZ's national curriculum framework. The implication of the early identification process was discussed.